2021
DOI: 10.3390/cancers13051137
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA as Epigenetic Modifiers in Endometrial Cancer: A Systematic Review

Abstract: The objective of this systematic review is to summarize our current knowledge on the influence of miRNAs in the epigenetic deregulation of tumor-related genes in endometrial cancer (EC). We conducted a literature search on the role of miRNAs in the epigenetic regulation of EC applying the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The following terms were used: microRNA, miRNA, miR, endometrial cancer, endometrium, epigenetic, epimutation, hypermethylation, lynch, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 177 publications
4
22
0
Order By: Relevance
“…Further, analysis of miRNA-seq data from The Cancer Genome Atlas (TCGA) database expanded the list of dysregulated miRNAs to 531 [ 179 ]. Previous systematic reviews identified, respectively, 106 miRNAs [ 183 ], 261 miRNAs [ 184 ], 310 miRNAs [ 185 ] dysregulated in ECs. However, these studies included also many miRNAs detected by high throughput methods, including microarrays and small RNA-seq, without confirmation by the RT-qPCR method that is a gold standard for miRNAs analysis [ 186 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, analysis of miRNA-seq data from The Cancer Genome Atlas (TCGA) database expanded the list of dysregulated miRNAs to 531 [ 179 ]. Previous systematic reviews identified, respectively, 106 miRNAs [ 183 ], 261 miRNAs [ 184 ], 310 miRNAs [ 185 ] dysregulated in ECs. However, these studies included also many miRNAs detected by high throughput methods, including microarrays and small RNA-seq, without confirmation by the RT-qPCR method that is a gold standard for miRNAs analysis [ 186 ].…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 is targeted by miR-26a and miR-101, which are downregulated in EC [42,46]. Importantly, epigenetic alterations affect miRNAs profile in EC [185]. It was found that loci of genes coding oncomiRNAs miR-130a/b, miR-182, miR-200b, miR-208a, miR-222, miR-625 are hypo-methylated in EC while genes of tumor-suppressor miRNAs miR-34b, miR-124a-1, miR-124a-2, miR-124a-3, miR-129-2, miR-137, miR-152, miR-638, miR-663 are hyper-methylated [185].…”
Section: Epigeneticsmentioning
confidence: 99%
“…MiRNAs in gynaecological diseases have also been reviewed [ 60 , 61 , 62 ]. However, the endometrium has often been overlooked in reviews concerning miRNAs, except when endometrial miRNAs are related to endometriosis [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] or endometrial cancer [ 71 , 72 , 73 , 74 , 75 , 76 ]. The remainder of this paper thus focuses on miRNAs in endometrial receptivity which has not been reviewed previously.…”
Section: Micrornas and Endometrial Receptivitymentioning
confidence: 99%
“… 29 , 30 , 31 , 32 , 33 , 34 , 35 However, in most of these, especially when focused on miRNAs, deregulation was observed by comparing tumor with normal counterpart or healthy tissue. 36 In this context, among others, a complete overview is presented by Srivastava et al, who reviewed the miRNAs differentially expressed in EC with respect to normal endometrial tissue. 37 On the contrary, the studies that analyzed miRNA expression taking into account other parameters, such as grade or the existing classifications schemes, particularly the TCGA one, are limited and with small consensus.…”
Section: Mirnas In Ecmentioning
confidence: 99%